Agile project management with Scrum: A case study of a Brazilian pharmaceutical company IT project. Issue 1 (4th January 2017) - Azanha, Adrialdo; Argoud, Ana Rita Tiradentes Terra; Camargo Junior, João Batista de; Antoniolli, Pedro Domingos
Abstract : Purpose: The purpose of this paper is to analyze the benefits of the agile project management (APM) framework compared to the traditional waterfall model, and understand how it can help companies add value and gain competitive advantage. Design/methodology/approach: The methodology used was the exploratory qualitative research through a case study of a software project, developed with the support and application of the Scrum framework, in a pharmaceutical industry information technology project. Findings: There were benefits found in the utilization of the agile framework, such as increased motivation and staff satisfaction, better control of requirements and especially higher quality of the delivered system, generating added value to the organization. Additionally, the project allowed the use of features from the first month of the application deployed, enabling a 75 percent reduction in development time, compared to traditional methods. The software development time was four months, 30 percent of what would be the total if the traditional methodology was adopted. Based on the results, the agile framework, especially the Scrum, proved to be a viable option as a project management approach. Research limitations/implications: Since this research is an exploratory case study, its results cannot be generalized. Practical implications: The paper provides relevant practical information and experiences to managers interested in implementing APM, as well as those interested in improving the management of projects. Originality/value: This paper provides a case study with practical implications of using APM, and APM's benefits and advantages are compared with the traditional waterfall approach. Companies can use this case study to better understand about the advantages and strengths of APM over the traditional approach.